Discovery of a Pederin Family Compound in a Nonsymbiotic Bloom-Forming Cyanobacterium - Kust, Andreja; Mareš, Jan; Jokela, Jouni; Urajová, Petra; Hájek, Jan; Saurav, Kumar; Voráčová, Kateřina; Fewer, David P; Haapaniemi, Esa; Permi, Perttu; Řeháková, Klára; Sivonen, Kaarina; et al. (ACS chemical biology, 2018)
The pederin family includes a number of bioactive compounds isolated from symbiotic organisms of diverse evolutionary origin. Pederin is linked to beetle-induced dermatitis in humans, and pederin family members possess potent antitumor activity caused by selective inhibition of the eukaryotic ribosome. Their biosynthesis is accomplished by a polyketide/nonribosomal peptide synthetase machinery employing an unusual trans-acyltransferase mechanism. Here, we report a novel pederin type compound, cusperin, from the free-living cyanobacterium Cuspidothrix issatschenkoi (earlier Aphanizomenon). The chemical structure of cusperin is similar to that of nosperin recently isolated from the lichen cyanobiont Nostoc sharing the tehrahydropyran moiety and major part of the linear backbone. However, the cusperin molecule is extended by a glycine residue and lacks one hydroxyl substituent. Pederins were previously thought to be exclusive to symbiotic relationships. However, C. issatschenkoi is a nonsymbiotic planktonic organism and a frequent component of toxic water blooms. Cusperin is devoid of the cytotoxic activity reported for other pederin family members. Hence, our findings raise questions about the role of pederin analogues in cyanobacteria and broaden the knowledge of ecological distribution of this group of polyketides.
Keywords: Symbiosis; sinice; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; multigenová rodina; Polyketides; Cyanobacteria; bakteriální geny; Multigene Family; polyketidy; symbióza; Peptide Synthases; Tandem Mass Spectrometry; Polyketide Synthases; peptidsynthasy; Genes, Bacterial; tandemová hmotnostní spektrometrie; hmotnostní spektrometrie s elektrosprejovou ionizací; polyketidsynthasy; Spectrometry, Mass, Electrospray Ionization